Tracing the evolution of ancient Chinese military science through classical texts - Mengcheng Wu; Dongbo Wang (Heritage Science)
Abstract The diachronic evolution of ancient Chinese military science is replete with profound philosophy and rich practical experience. This paper aims to delve into the diachronic evolution of the content of ancient Chinese military texts from the perspective of information science, utilizing information technology to address the primary research problem of how ancient military thought and practices evolved over time. By collecting representative military texts from various historical periods in China and supplementing the data with translations via machine translation technology, a comprehensive corpus of ancient Chinese military texts has been constructed. Based on this corpus, various methods such as BERTopic topic modeling, automatic summarization, and named entity recognition have been employed to meticulously explore and analyze the themes, ideas, and technologies within these ancient military texts. The results indicate that the inheritance of the ideas from “The Art of War” by Sun Tzu is primarily concentrated in the Warring States period and the Song and Yuan dynasties. Moreover, the themes and technologies in ancient Chinese military texts exhibit a trend of gradual enrichment and diversification over the course of history.